The role of the virtual tutor in distance education - Márcia Gorett Ribeiro Grossi; José Wilson Costa; Mércia Maria Moreira (Universidade Federal de Santa Maria, 2013)
The Distance Education is gaining prominence in today's society, due to emergency of the information technologies and the increasing need for knowledge. Considering that the technologies used in distance education will not ensure the success of this teaching modality theirselves, we highlight the figure of the virtual tutor. In this perspective, the objective of this research was to investigate the functions of virtual tutor as an adjunct in the process of teaching and learning, as well as the limits of their professional practice, through a case study in two schools, one public and one private. It was possible to understand some peculiar characteristics of the virtual tutors' work and to make some inferences, specially about the need for a closer look into the activities of such professionals and their regulamentation.